Analisis Konten Visual Instagram dalam Membangun Keterlibatan Pelanggan: Studi Kasus Akun Instagram X Food and Beverage - Nur'ain Suleman; Rizan Machmud; Syamsul B. Biki (Transbahasa, 2026)
Amidst the rapid growth of the culinary industry, Instagram has become a primary brand communication instrument that demands visual excellence to attract audiences. This study aims to analyze the role of visual aesthetics on the X Food and Beverage Instagram account in shaping customer engagement. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews with seven informants (management, admins, and loyal consumers) and visual documentation of the research object. The analysis examined visual elements such as the earth-tone color palette and minimalist composition through semiotic theory. The findings indicate that consistent visual usage successfully established a strong brand identity and provided a sense of mindfulness for the audience, effectively increasing trust in product quality. However, a